2020
DOI: 10.3892/ijmm.2020.4524
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of rat adipose‑derived stem cells differ under normoxic/physioxic conditions and are�associated with paracrine factor secretion

Abstract: Adipose tissue-derived stem cells (AScs) are beneficial for myocardial regeneration. The physiological oxygen content of human organs is estimated to range between 1 and 11%. However, in the majority of previous in vitro studies with cultured ASCs, the O 2 concentration was artificially set to 21%. The present study aimed to compare the protective effects of rat ASCs on neonatal rat ventricular myocytes (NRVMs) under normoxic (21% O 2 ) and physioxic (5% O 2 ) conditions. Rat NRVMs cultured under normoxia or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Therefore, most of the contemporary experiments using in vitro cell culture are conducted with oxidatively stressed cells. Culture in hyperoxic conditions has conferred a protective resilience to many kinds of oxidative stressors, which is thought to be an artefact arising from the current culture leading to poor translation of investigations from in vitro to in vivo (Ferguson et al, 2018;Lin et al, 2020). On the contrary, the extent of antioxidant enzyme activities and redox homeostasis are examined to be closer to in vivo conditions if the cells are pre-conditioned under physioxia (Pastore et al, 2001;Shindo et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most of the contemporary experiments using in vitro cell culture are conducted with oxidatively stressed cells. Culture in hyperoxic conditions has conferred a protective resilience to many kinds of oxidative stressors, which is thought to be an artefact arising from the current culture leading to poor translation of investigations from in vitro to in vivo (Ferguson et al, 2018;Lin et al, 2020). On the contrary, the extent of antioxidant enzyme activities and redox homeostasis are examined to be closer to in vivo conditions if the cells are pre-conditioned under physioxia (Pastore et al, 2001;Shindo et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…showed that coculture with ASCs protects neonatal rat ventricular myocytes from apoptosis caused by H 2 O 2 treatment and significantly reduces oxidative stress under normoxic and hyperoxic conditions [ 29 ]. The protective effect of ASCs is related to increasing secretion of VEGF, IGF-1, and bFGF [ 30 ]. Additionally, extracellular vesicles secreted by ASCs attenuate PM2.5-induced apoptosis and necrosis of alveolar type II epithelial cells and improve lung injury and pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%